Faktor-Faktor yang Mempengaruhi Leverage pada Perusahaan Food and Beverage yang Terdaftar di BEI Periode 2020–2024 - Muhamat Fahruddin; Moh. Miftaqul Ihsan; Sisca Aprilia; Isanaini Rahmatul Mujahidah (JURNAL RISET MANAJEMEN (JURMA), 2025)
This study aims to analyze the factors influencing leverage in food and beverage companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Using a quantitative approach, this study involved a purposive sampling technique on three companies: PT Sariguna Primatirta Tbk, PT Indofood Sukses Makmur Tbk, and PT Mulia Boga Raya Tbk. Variables included liquidity, profitability, business risk, asset structure, and company size, using descriptive financial analysis. The results show that liquidity and profitability have a negative effect on leverage, which is in line with the pecking order theory, which states that companies prefer internal financing over debt. Furthermore, companies with high business risk tend to reduce the use of debt. Meanwhile, asset structure and company size do not show a consistent effect on leverage. These findings suggest that corporate leverage policies are more influenced by internal factors, such as the financial strategy implemented by the company, rather than external or market factors. This provides further insight into leverage management in the Indonesian food and beverage sector.